K-ras peptide mimotope induces antigen specific Th1 and B-cell immune responses against G12A-mutated K-Ras antigen in balb/c mice - Siak, Pui Yan; Wong, Kuan Yee; Song, Adelene Ai Lian; Abdul Rahim, Raha; Lian, Lionel Aun In (Multidisciplinary Digital Publishing Institute, 2021)
KRAS G12A somatic point mutation in adenocarcinomas is categorized clinically as ineligibility criteria for anti-epidermal growth factor receptor (EGFR) monoclonal antibody therapies. In this study, a modified G12A-K-ras epitope (139A) with sequence-specific modifications to improve immunogenicity was developed as a potential vaccine against G12A-mutant KRAS cancers. Additionally, coupling of the 139A epitope with a tetanus toxoid (TTD) universal T-cell epitope to improve antigenicity was also reported. To facilitate convenient oral administration, Lactococcus lactis, which possesses innate immunomodulatory properties, was chosen as a live gastrointestinal delivery vehicle. Recombinant L. lactis strains secreting a G12A mutated K-ras control and 139A with and without TTD fusion were generated for comparative immunogenicity assessment. BALB/c mice were immunized orally, and high survivability of L. lactis passage through the gastrointestinal tract was observed. Elevations in B-cell count with a concomitant titre of antigen-specific IgG and interferon-γ secreting T-cells were observed in the 139A treated mice group. Interestingly, an even higher antigen-specific IgA response and interferon-γ secreting T-cell counts were observed in 139A-TTD mice group upon re-stimulation with the G12A mutated K-ras antigen. Collectively, these results indicated that an antigen-specific immune response was successfully stimulated by 139A-TTD vaccine, and a TTD fusion was successful in further enhancing the immune responses.